Inovasi Pemasaran MTS Daarul Rahman V Sungai Guntung Indragiri Hilir, Riau - Nurul Adha; Akhmad Sunhaji; Syamsul Bahri Tanrere (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This thesis concludes about Educational Service Marketing Innovation in Increasing the Interest of MTS Daarul Rahman V Students in Sungai Guntung Indragiri Hilir, Riau. This study uses a qualitative approach, with data collection through interview, observation, and document study techniques. The results of these findings reveal several things as follows: First , the Marketing carried out by MTS Daarul Rahman V Sungai Guntung Indragiri Hilir Riau has implemented various integrated marketing strategies. They made direct visits to schools around the Guntung River area, where the ustadz, ustazah, and students introduced the advantages of Islamic boarding schools. Islamic boarding schools also take advantage of religious events such as the commemoration of maulid and isra' mi'raj for da'wah, as well as participating in the Quranic tilawatil contest. In addition, they use print media such as brochures and banners. The involvement of students in extracurricular activities such as scouting and skill demonstrations such as calligraphy is also part of an effective marketing strategy to attract interest and strengthen the positive image of the Islamic boarding school. Second , marketing innovation efforts to increase interest in MTS Daarul Rahman V Sungai Guntung Indragiri Hilir Riau include the use of technology and digital platforms, especially social media, which is the key to reaching a wider audience and increasing public awareness. The use of the latest technology in marketing can improve the efficiency of information delivery and services. The development of an effective promotion strategy and the upskilling of the marketing team are also crucial. Focusing on compelling visual marketing can increase the situational interest of prospective students.